Statistical methods for the analysis of earnings data : with special application to salaries in Swedish industry - Klevmarken, Anders (Stockholm : Almqvist & Wiksell, 1972)
In this study two different (but related) approaches are suggested for the analysis of earnings data. The first approach is a combined time series and cross section analysis of age-earnings profiles by educational qualification, the second is a more detailed investigation of the earnings structure in a cross section. As an illustration they are applied to salary data from Swedish industry.
Extra t.p. with thesis statement, inserted.
At head of title: Industrial Institute for Economic and Social Research.
Bibliography: p. 267-271.
hza
Loans
Keywords: Wages